Parturition is Not the Mirror Image of Implantation: The Role of Progesterone (Global Journal of Medical Research, 2023)
There has been an abundance of evidence from clinical animal and in vitro studies that progesterone P4 is important for establishing maintaining and terminating a pregnancy P4 exerts its primary action via its two receptors progesterone receptor A PGR-A and B PGR-B Analyses of transcriptome and cistrome genome have unearthed novel members and modifiers of the P4 signaling pathway The increase in serum P4 levels and down-regulation of PGR-B are important in the development of pinopodes thus marking implantation Additionally it promotes the quiescent myometrial cell phenotype and the inhibition of its production in myometrial cells induces labor and is the key physiologic initiator of parturition Through genomic and non-genomic intracellular mechanisms involving these PGR isoforms various physiologic states can be determined such as the quiescent and contractile myometrium during pregnancy
Keywords: progesterone; implantation; parturition; progesterone receptor; PGR gene; genetic pathways